Peran Pemerintah dalam pembangunan hotel di Kota Jayapura - Nelman Rumere; Nyoman Ariana; IGN Widyatmaja (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2018)
Abstract The hospitality industry in Jayapura City has increased. Therefore, the role of government is expected in the making of hotel development regulation, as the facilitator of hotel development, as the supervisor of hotel development, and the role of government in the development of special human resources of government technical personnel. Constraints to the implementation of government policies in hotel development, namely internal constraints and external constraints. The purpose of this research is to know the role of government in hotel development and the constraints of government policy implementation in hotel development in Jayapura City. Data collection in this research is done by observation, interview of documentation study and literature study. Determination of informants is done by purposive sumpling, informant in this research, that is official of local government of Jayapura City. The collected data is analyzed descriptively qualitative. The results of the discussion show the role of the government in the construction of hotels, as regulators, facilitators, supervisors, and the development of specialized human resources of government technical personnel. The obstacles of government policy implementation in hotel construction are internal constraints such as special human resources of government technical personnel, budget or fund, coordination among government agencies, and enforcement of regulation. External constraints include, central regulation, Papua Province's regulatory, investor, long-stay tourists, and tourism industry data inventory. Suggestions given, the need for regulation of hotel development, hotel supervision, the provision of facilities and infrastructure, the budget devoted to the government of hotel infrastructure improvements, and the role of government in improving the special human resources of government technical personnel. Keywords: Government, Hotel